The Potential of Natural Resources in Advanced the Tourism Sector in the Global Economic Era in Indonesia - Alan Rakhmat Putra; Jotha Scorda; Ayu Rakmawati Oktavia; Johannes Johannes (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Natural resource potential plays a crucial role in supporting the development of the tourism sector in the global economic era. Natural resources such as beaches, mountains, forests, lakes, and biodiversity are key attractions that drive both domestic and international tourist visits. This article aims to analyze the potential of natural resources in advancing the tourism sector and their impact on community economic growth. The research employed a qualitative descriptive method with a literature study approach, collecting data from relevant journals, books, and other scientific sources. The study's findings indicate that optimal natural resource management can enhance the competitiveness of tourist destinations, create jobs, increase community income, and encourage regional development. However, challenges such as environmental damage, lack of infrastructure, and low public awareness of the importance of nature conservation remain obstacles to the development of sustainable tourism. Therefore, synergy between the government, communities, and the private sector is needed to manage natural resource potential sustainably so that the tourism sector can develop optimally amidst global economic competition.